The Effect of Robinson’s Strategy on Achievement and Mathematical Strength among First Intermediate Students in Mathematics - Resan Al-waily, Azhar Abid (Opción, 2019)
The aim of the present research is to identify the effect of Robinson’s strategy on achievement and mathematical strength among the first middle students in mathematics. The sample consisted of (64) students of the first intermediate students in (Mohammed Al-Baqir Boys’ Secondary) of the Directorate of Ed- ucation in Dhi- Qar by (33) students in the experimental group (31) students in the control group. The achievement test was prepared by (40) items. (32) substantive paragraphs and (8) paragraphs, the apparent validity of the test and the validity of the content were calculated and the stability coefficient of the test was calculated using the Alpha-Kronbach equation (0.81). The appar- ent validity and constructively were verified and the stability coefficient was used by Coder Richardson 20 equation (0.88). Using the appropriate statis- tical methods, the results showed that the experimental group students who studied according to the Robinson strategy were superior to the control group students who studied in the usual way in the achievement test. Results A number of conclusions , recommendations and proposals were reached.